Laser capture microscopy. Issue 2 (1st April 2000) - Curran, S; McKay, J A; McLeod, H L; Murray, G I
Abstract : Human tissues are composed of complex admixtures of different cell types and their biologically meaningful analysis necessitates the procurement of pure samples of the cells of interest. Many approaches have been used in attempts to overcome this difficulty, including a variety of microdissection methods. This review concerns a recent advance in microdissection techniques, namely laser capture microdissection (LCM). The principle underlying this technique is outlined, and practical issues pertaining to LCM are considered. In addition, the literature relating to LCM is reviewed, with examples of research applications of this technique being outlined.